玉米肽对小鼠酒精性脑损伤的保护作用及其机制Protective effect of corn peptide on alcoholic brain injury in mice and its mechanism - 林巍，曲国强，刘晓兰，任健LIN Wei，QU Guoqiang，LIU Xiaolan，REN Jian (Zhongguo youzhi, 2022)
建立小鼠慢性酒精性脑损伤模型，研究玉米肽对酒精性脑损伤的保护作用。将ICR小鼠随机分为 5 组，分别为正常对照组、慢性酒精性脑损伤模型组、玉米肽高剂量组（2 g/kg）、玉米肽中剂量组（1 g/kg）、玉米肽低剂量组（0.5 g/kg）。采用直接饮用酒精溶液法建立小鼠慢性酒精性脑损伤模型，同时实验组小鼠给予玉米肽，连续5个月，实验结束后取脑组织，进行病理组织学观察，同时采用酶联免疫试剂盒检测各组小鼠脑组织中氧化应激相关指标和促炎细胞因子水平，此外还测定了小鼠脑组织中部分凋亡相关指标。结果表明：脑病理组织学显示玉米肽低、中、高剂量组能够不同程度地减轻酒精对小鼠脑组织的损伤作用；氧化应激指标表明玉米肽能够提高小鼠脑组织中GSH含量，增加GST、GSH-Px和T-SOD活性，降低MDA含量，减少细胞中ROS含量（P<0.05）；此外玉米肽还能够显著降低小鼠脑组织中TNF-α、IL-6、IFN-γ、TGF-β1和NF-κB水平（P<0.05）。玉米肽不仅通过调节酒精引起的神经细胞氧化应激，而且通过下调促炎细胞因子水平而改善小鼠酒精性脑损伤。 The alcoholic brain injury mouse model was established, and the protective effect of corn peptide on the alcoholic brain injury was studied. ICR mice were randomly divided into 5 groups: normal control group, alcohol model group, high dose corn peptide group(2 g/kg), medium dose corn peptide group(1 g/kg) and low dose corn peptide group(0.5 g/kg). The alcoholic brain injury mouse model was induced by drinking alcoholic solution, then the mice in the experimental group were given corn peptide for 5 months. The brain tissue was taken for histopathological observation and ELISA mensuration, including oxidative stress-related indicators, inflammatory cytokines levels and some apoptosis-related indicators. The results showed that the histopathology indicated that the alcoholic brain injury was reduced to different degree in low, medium and high dose corn peptide groups. The results of oxidative stress indexes indicated that corn peptide could increase the content of GSH and the activities of GSH-Px and T-SOD, and decrease the contents of MDA and ROS （P<0.05）. In addition, the levels of TNF-α, IL-6, IFN-γ, TGF-β1 and NF-κB in brain tissue were significantly decreased （P<0.05） by corn peptide. In conclusion, corn peptide ameliorated alcoholic brain damage not only by regulating oxidative stress of nerve cell, but also by reducing proinflammatory cytokines levels.